Working it out Career Guidance and Employer Engagement - Musset, Pauline (OECD Publishing, 2018)
Career and education decisions are amongst the most important young people make. Gender, ethnicity and socio-economic factors all strongly affect these choices. Career guidance is both an individual and a social good: it helps individuals to progress in their learning and work, but it also helps the effective functioning of the labour and learning markets, and contributes to a range of social policy goals, including social mobility and equity. This justifies the public investment in career guidance activities. Empirical evidence point towards career guidance services - in school and outside - having a formative influence on young people's understanding of themselves and the world of work, and can often improve educational, social and economic outcomes. As young people stay in education and training longer and as the labour market becomes more complex, the case for career guidance grows. But what makes for effective provision? This paper looks at the features of good career guidance practice, including the need for schools to begin early and the essential role of exposure to the world of work
Keywords: Education